Characterization of a typology of exercises for the teaching of the Model Entity/Relationship - Manuel Pereira Rosa (Revista MENDIVE, 2007)
The creation process of a database crosses through a series of stages; one of them is the design. Inside this stage the data models play an important role. This article shows a characterization of a typology of exercises to work in the teaching-learning process of the pattern entity/relation and its use in the relational database design.